(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the un-booked obstetric patients and their outcome presenting at Sheikh Zaid Hospital Rahim Yar Khan. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynecology Sheikh Zaid Hospital Rahim Yar Khan from March 2016 to September 2016. Materials and Methods: Total 182 un-booked obstetric patients having age 18 to 35 years were selected. Patients having age >35 years, patients with any systemic disease like diabetes mellitus and hypertension on previous medical record, patients with ruptured uterus on the basis of history and examination, patients with 2 or more C-sections were excluded from the study. Women who have never attended or attended antenatal clinics only once or twice were considered as un-booked cases. Results: Mean age of the patients was 26.87 ± 6.49 years. Total cases 82 (45%) were booked and un-booked cases were 100 (55%). Total vaginal deliveries were 71 (39%) and caesarean section was performed in 111 (61%) cases. Family income of 97 (53%) cases was Rs. <15000, family income of 57 (31.3%) cases was Rs. 15001 – 30000 and family income of 28 (15.4%) cases was Rs. >30000. Total 101 (55%) cases were primary para and 81 (45%) cases were multipara, 116 (64%) belonged to rural area and 66 (36%) belonged to urban area. Conclusion: In present study, high percentage of un-booked obstetrics was noted and in most of the cases c-section was performed. Insignificant association of mode of delivery with age, income status, area of residence and parity was noted. But significant association between education status and mode of delivery was observed.